Preserving humanity or surrendering it? Grammarly adoption a site of cultural-pedagogical negotiation in transnational education - Duffy, Liam; Lin, Binghang (Journal of International Students, 2026)
Using a Sino-American university in mainland China as a comparative lens against findings from North America, Europe, and Southeast Asia, this qualitative study examines the sharply polarized adoption of an institution-wide Grammarly EDU license. Despite free access, Chinese students and nonnative academic staff adopted Grammarly as an essential tool, while many native-speaking academic staff resisted it on philosophical grounds. A third pattern, positioning Grammarly as the ethically "safe" AI alternative to generative tools, emerged across various contexts. The paper argues that transnational campuses function as accelerated laboratories for negotiating the global boundary between corrective and generative AI in writing pedagogy. The findings contribute to internationalization theory by revealing how tool adoption becomes a proxy for deeper cultural contests over legitimate academic labor.